Capping-ligand free grinding synthesis of luminescent lead halide perovskite nanocrystals. (March 2021) - Zhang, Ting; Jiang, Chunli; Luo, Rong; Qi, Ruijuan; Liu, Mengqin; Luo, Chunhua; Lin, Hechun; Peng, Hui
Graphical abstract: A luminescent lead halide perovskite, (TMBM)PbBr3, is prepared by the simple grinding without using any capping ligand, whose emission can be enhanced by the addition of small amount of water and methanol. Highlights: A green mechano-grinding method is developed to prepare luminescent lead halide perovskites nanocrystals. Introducing water or methanol can enhance the luminescence of (TMBM)PbBr3 nanocrystals. The emission of (TMBM)PbBr3 nanocrystals can be tuned by the doping of chloride ion. Abstract: Luminescent (trimethylbromomethyl) ammonium lead tribromide ((TMBM)PbBr3 ) nanocrystals are synthesized by a green single-step mechano-grinding method in large scale. The photoluminescence quantum yield (PL QY) of the obtained (TMBM)PbBr3 nanocrystals is 2.61 %. The luminescence of the nanocrystals can be significantly enhanced by introducing water or methanol during the grinding process. The maximum PL QYs of 7.65 % and 4.69 % are obtained for the nanocrystals prepared by the addition of water and methanol, respectively. The emission light of (TMBM)PbBr3 nanocrystals can be tuned by the doping of chloride ion.